Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1177/1559827619844505
|View full text |Cite
|
Sign up to set email alerts
|

Catalysts for Change: Accelerating the Lifestyle Medicine Movement Through Professionals in Training

Abstract: While the Western diet has evolved to become increasingly high in saturated fat, cholesterol, protein, sugar, and salt intake, nutrition education and training of health care professionals to counsel their patients on the hazards of such a diet has trailed behind. Primary care physicians have an opportunity to bridge the gap by providing nutrition and dietary counseling as key components in the delivery of preventive services. Increasing research points to the value of a whole-foods plant-based diet in combati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Reasons for excluding articles reviewed as full-text included wrong study design (n=10), [11][12][13][14][15][16][17][18][19][20] wrong population (n=2), 21 a failure to report any outcome measures (n=2), 8,22 wrong intervention (n=3), [23][24][25] and two studies were found to be a duplicate data set. 26,27 Of the 12 included studies, the majority were qualitative studies (n=4) [28][29][30][31] or cross-sectional studies (n=4); [32][33][34][35] and the remainder were prospective case series studies (n=2), 36, 37 a case study (n=1) 38 and a mixed-methods study (n=1).…”
Section: Resultsmentioning
confidence: 99%
“…Reasons for excluding articles reviewed as full-text included wrong study design (n=10), [11][12][13][14][15][16][17][18][19][20] wrong population (n=2), 21 a failure to report any outcome measures (n=2), 8,22 wrong intervention (n=3), [23][24][25] and two studies were found to be a duplicate data set. 26,27 Of the 12 included studies, the majority were qualitative studies (n=4) [28][29][30][31] or cross-sectional studies (n=4); [32][33][34][35] and the remainder were prospective case series studies (n=2), 36, 37 a case study (n=1) 38 and a mixed-methods study (n=1).…”
Section: Resultsmentioning
confidence: 99%
“…Many student and trainee leaders have contributed to this work, but scholarly activity in this area has particularly been advanced by Dr Beth Frates, Dr Mark Faries, Dr Sami Beg, Dr Edward Phillips, Dr Tonya Cramer, Dr Brenda Rea, Dr Jennifer Trylk, and Dennis Muscato through their support of Professionals in Training through initiatives such as the Donald Pegg award, the Lifestyle Medicine Residency Curriculum, and LMed. 16 The influence of epigenetics is another theme that we see throughout the conference and this issue. Epigenetics makes that case that genes are not destiny, and it is becoming increasingly clear that, in the era of personalized medicine, epigenetics is the science that will help make the case for lifestyle interventions as a mediator of gene expression.…”
mentioning
confidence: 90%
“…Many student and trainee leaders have contributed to this work, but scholarly activity in this area has particularly been advanced by Dr Beth Frates, Dr Mark Faries, Dr Sami Beg, Dr Edward Phillips, Dr Tonya Cramer, Dr Brenda Rea, Dr Jennifer Trylk, and Dennis Muscato through their support of Professionals in Training through initiatives such as the Donald Pegg award, the Lifestyle Medicine Residency Curriculum, and LMed. 16…”
mentioning
confidence: 99%
“…Oral health food knowledge has been studied in a range of health professionals [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. The classification of foods as healthy or otherwise was in accordance with recommendations and advice outlined in government-endorsed dietary guidelines for healthy eating of the respective countries of study [ 42 , 47 , 48 , 49 , 50 , 51 ].…”
Section: Introductionmentioning
confidence: 99%